Konstruksi Seksualitas Perempuan di Majalah Men’s Health - ARDIANSYAH, ARIEF SOFYAN (Komunikator, 2012)
This study explores the construction of female sexuality in MEN’S HEALTH Magazine. MEN’S HEALTH is a magazine which contains information about fitness, health, intimacy, career and fashion. MEN’S HEALTH in Indonesian edition is a franchise of Indonesian Edition which is licensed by the United States’ MEN’S HEALTH. The purpose of this study is to study the construction of female sexuality in the media. This study also aims to examine the imbalance of power between men and women which is built by the media. By using critical discourse analysis, this research shows that woman’s sexuality is under men’s domination, and it is exploited by capital. There are several points in the conclusion which are women as commodity and women as ones who were defeated. According to MEN’S HEALTH, good women are asexual and it exploits sexuality as an object. MEN’S HEALTH degrades women’s bodies and states that women are subordinate to men. Keywords: Sexuality, Intimacy, Gender, Critical Discourse Analysis, Ideology